Why do Pit-Hours outlive the Pit? - Sait R. Ozturk; Michel van der Wel; Dick van Dijk (Tinbergen Institute, 2015)
We study why a majority of trades still happen during the pit hours, i.e. when the trading pit is open, even after the pit ceased to be a liquid and informative venue. We investigate the case of 30-year U.S. Treasury futures using a ten-years-long intraday data set which contains the introduction of the CME Globex platform as an example of sophistication in electronic trading. We use a structural model to estimate the time-variation in potential factors of the clustering of trading activity around the pit hours, namely price informativeness, information asymmetry and price impact of trades. We find evidence for a feedback mechanism between trading activity and these factors. Across the sample period, price informativeness during the afterhours is a consistently significant factor attracting trade activity. Information asymmetry has a negative effect on afterhours act ivity, particularly during the crisis years. The negative effect of price impact on afterhours activity ceases to be a significant factor from 2007 on, possibly due to improvements in order execution algorithms and electronic trading facilities.
Keywords: C32; G14; 330; Afterhours Trading; Market microstructure; Kalman filter